Advanced Strategies in Synthesis of Two‐Dimensional Materials with Different Compositions and Phases. Issue 4 (5th February 2023) - Yang, Yang; Jia, Lin; Wang, Dainan; Zhou, Jiadong
Abstract: In recent years, 2D materials—M a X b with different compositions and phases have attracted tremendous attention due to their diverse structures and electronic features. The common thermodynamically stable 2H and metastable 1T phases have been extensively studied, however, there are many unusual compositions and phases with novel physical properties that have yet to be explored. Therefore, summarization of the synthesis strategies, atomic structures, and the unique physical properties of 2D materials with different compositions and phases is very important for their development. In this review, the strategies including chemical vapor deposition, intercalation, atomic layer deposition, chemical vapor transport, and electrostatic gating for synthesizing various 2D materials with different phases and compositions are first summarized. Specially, the intercalation strategies including heterogeneous‐ and self‐intercalation for controllable phases and compositions fabrication are mainly discussed. Then, the novel atomic structures of 2D materials are analyzed, followed by the fascinating physical properties including ferroelectricity, ferromagnetism, superconductivity, and so on. Finally, the conclusion and outlook are offered including the challenges and future prospects of 2D materials with different compositions and phases. Abstract : This review first summarizes the synthesis strategies including chemical vapor deposition, intercalation, and so on. Then, the novel atomic structures of 2D materials are analyzed, followed by the fascinating physical properties including ferroelectricity, ferromagnetism, and superconductivity. Finally, the conclusion and outlook are offered including the challenges and future prospects of 2D materials with different compositions and phases.